Stand Up Comedy: Language Play and Its Functions (Systemic Functional Linguistic Approach) - I Dewa Putu Wijana (Universitas Sanata Dharma, 2016)
It is obviously misleading to regard that play-on-word activities are unimportant or trivial in human life. In many diverse societies, punning activities have very central roles in rituals as well as in cultural transformation processes. The importance of role played by punning activities attracts me to discuss the functions of language found in Stand Up Comedy, the most recent and popular comedy show broadcasted by Metro TV Station. This television program shows the skillfulness of comedians in telling jokes in front of its audience who are mostly teenagers or adolescents. Joking activities play central roles in human life because of their various functions, especially to criticize various social conditions that happen in the speakers community. However, to create unaggressive and constructive criticisms, the comedians build an intimate relation with their audience to create an effective deliverance. Consequently, they use certain moods of interaction using informal language styles which are full of ambiguities that can easily confuse audiences perceptions about many things. This is, of course, for the sake of eliciting audiences smiles and laughter. Keywords: stand-up comedy, language play, contextual framing